A systematic review on the effects of the Covid-19 pandemic on the food security in Malaysia / Mohd Zulhelmi Syafuddin Tan, Ahmad Naqiyuddin Bakar and Yarina Ahmad - Syafuddin Tan, Mohd Zulhelmi; Bakar, Ahmad Naqiyuddin; Ahmad, Yarina (2021)
The COVID-19 pandemic had provided many adverse effects on the economies of many countries and individuals around the world. Economic downturns always led to a rising rate of hunger. World Bank (2021) reported that as of April 2021, around 296 million individuals are experiencing food insufficiency, an increment of 111 million more individuals if compared to April 2020, based on the data obtained in 35 countries where the World Food Programme works. Additionally, the United Nations Food and Agriculture Organization (FAO) estimates that the case of undernourishment increased drastically by 82 to 132 million people in 2020 due to the COVID-19 pandemic (Elias & Jambor, 2021). This scenario showed how severe the consequences of the COVID-19 pandemic are to the food security threat, especially in the availability dimension. The number of people encountering a heightened level of food insecurity in 2020 and 2021 is anticipated to have radically increased. Hence, the threat to food availability in the post-COVID-19 era is an unpredictable phenomenon and has a robust effect on global food security. This threat might contribute to rising numbers of hunger and undernutrition, leading to adverse health-related consequences acute effect on livelihood caused by the COVID-19 pandemic is a phenomenon that happened globally, affecting the world socially and economically, creating a threat to food security, and does not spare Malaysia.